DAMPAK LAHAR PASCA ERUPSI MERAPI TERHADAP INFRASTRUKTUR: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Zainul Faizien Haza; Angga Darmawan; Febriana Ramadhani (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2026)
The 2010 eruption of Mount Merapi (VEI 4) did not only cause immediate impacts during the event, but also triggered post-eruption rain-triggered lahar (volcanic mudflow) hazards that persisted for years. This systematic literature review aims to identify the characteristics and level of infrastructure damage caused by the post-eruption lahars of Merapi 2010, as well as the factors influencing them. A search was conducted across the Scopus, ScienceDirect, SpringerLink, Garuda, and grey literature databases (BNPB, BPBD, Ministry of PUPR, JICA) using the PRISMA protocol. Out of 275 identified articles, 12 studies met the inclusion criteria and were analyzed narratively. The synthesis results show that infrastructure damage reached over 1,167 housing units, 31 to 34 bridge units, and 77 sabo dam units (29% of total assets). The Yogyakarta-Semarang national road experienced accessibility disruptions 18 times. The main factors influencing the level of damage were dynamic flow pressure (weak structures collapsed at 5 kPa), flow velocity (greater than 3 m/s), and the mismatch between the sabo dam design capacity (1.75 million m³) and the actual lahar volume (greater than 5 million m³). A lahar event in Senowo in March 2026 proves that the risk remains active 16 years post-eruption. The conclusion of this study emphasizes the need to revise sabo dam designs for VEI 4 scenarios and to integrate a rainfall-based early warning system (greater than 20 mm/hour). Keywords: or volcanic mudflow, infrastructure, sabo dam, Mount Merapi, systematic literature review